MODEL PENENTUAN JUMLAH PESANAN PADA AKTIFITAS SUPPLY CHAIN TELUR AYAM MENGGUNAKAN FUZZY LOGIC - Santosa, Sesar Husen; Hidayat, Agung Prayudha (Jurnal Ilmiah Teknik Industri, 2019)
This study aims to present a fuzzy logic approach in the modeling of optimal order quantities of chicken eggs to suppliers. Determination of the number of egg orders using fuzzy logic by considering the condition of supply and demand so that the number of eggs ordered by Agent eggs is optimal so that the amount of stock in the warehouse is reduced. The variables used in developing the fuzzy set model are the price of eggs/crates, the composition of the weight of eggs in the crates, and the amount of stock of eggs in the warehouse at the time of ordering. The membership set for egg ordering uses the Triangular and Trapezoidal membership functions. The fuzzy set model produced in this study can be used as a tool for decision making in determining the optimal number of egg orders to suppliers.